Fenestrated Endografting After Bare Metal Dissection Stent Implantation. (April 2015) - Barbante, Matteo; Sobocinski, Jonathan; Maurel, Blandine; Azzaoui, Richard; Martin-Gonzalez, Teresa; Haulon, Stéphan
Purpose: To present a case that demonstrates the ability to deploy a 4-fenestrated endograft in an aorta previously treated with an endovascular graft and additional distal bare stents for acute type B dissection.Case Report: Five years ago, a 61-year-old man had a Zenith TX2 endovascular graft and 2 distal bare metal stents deployed for acute type B dissection. In follow-up, a distal extension endograft was deployed below the bare stent for false lumen reperfusion and aortic growth. The ascending aorta and the arch were replaced surgically at 3 years, with the distal end of the graft sewn to the existing endograft. At the current admission, a Crawford type III thoracoabdominal aortic aneurysm was found and excluded with a 4-fenestration endograft. Using 3-dimensional fusion imaging, there was no major conflict with the struts of the bare dissection stent during catheterization and bridging stent placement. A distal bifurcated endograft was also implanted. The total procedure time was 240 minutes, the radiation dose was 8066 cGy·cm 2, and the contrast volume was 100 mL. The patient was discharged on the sixth postoperative day and continues to do well at 9 months.Conclusion: Prior dissection stent deployment within the thoracoabdominal segment does not preclude further fenestrated endograft placement. Intraoperative fusion imaging can be very helpful to the successful completion of these complex procedures.